Integration of mahalanobis-taguchi system and time-driven activity-based costing for thermal printer in reducing variation - Nurul Haziyani, Aris (2024)
System integration is the process of creating or deploying a customized application or architecture, as well as combining packaged and customized software, communications, and new or pre-existing hardware. The thermal printer is ordinarily used for printing commercially available tags and labels from various manufacturers. The demand for electronic components is increasing. Thus, the preparation of weekly rejection report for rejected parts to indicate the severity level is needed. The severity level can contribute in deciding the parameters that can identify the significant factors. Meanwhile, the activitybased costing (ABC) approach currently in use is outdated since it relies on interviews or surveys to acquire numerical data, which might result in erroneous data for the company’s reference. As a result, time-driven activity-based costing (TDABC) is applied to various product complexity techniques. So, there are three elements that need to prioritize in business growth, which are time, quality, and cost. This is because, the integration between process (parameter) can give impact to the profit (cost). The primary objective of this study is to merge the Mahalanobis-Taguchi system (MTS) with the TDABC at an electronic component workstation. The data was gathered from an electronics company in Pasir Gudang, Johor, that specializes in printed circuit board (PCB) assembly manufacture. MTS optimizes a total of 22 parameters at the top-side workstation, which includes refrigerator temperature (°C), refrigerator humidity (%), room temperature (°C), and others. The sample data used for the parameter analysis is 2022. On the other hand, TDABC calculates underutilized capacity by taking into account the main factors provided by the time equation and capacity cost rate. The costs used in the calculation are annual costs. The resource costs to consider are labor costs, maintenance costs, material costs, and consumable costs. As a result, the analysis shows that there are MD threshold overlaps occurred between normal and abnormal for each month. This is because the sample of abnormal data has a small number parameters corresponding to the abnormal condition. In March, the centre of normal and abnormal MD threshold is 2.827 and 18.059 respectively. The June MD thresholds for normal and abnormal are 2.826 and 11.151, whereas the September MD thresholds are 3.000 and 183.137. The degree of contribution shows the highest significant parameters with 16 parameters is in October and December. In contrast, the least significant parameters with 10 parameters are in August. TDABC is then utilized to perform capacity utilization analysis in order to diagnose the used and unused capacity of time and cost. It is acknowledged that the PCB input into auto loader machine sub-activity has a high unused capacity of time (239,550 minutes) and cost (MYR18,120.67) which makes this workstation able to reduce the unused capacity by transferring the number of workers to another load workstation. On the contrary, additional labor should be provided in the solder paste preparation subactivity as it has overutilized capacity of time (-790,100 minutes) and cost (MYR1,000,535.13) in order to minimize the capacity utilization. Lastly, the system integration between degree of contribution using MTS and unused capacity utilization using TDABC has reduced the waste and improve forecasting for the company reference in the future.